Bioactive Compounds and Antioxidant Activity of Ethanol Leaf Extract of Eucalyptus Tereticornis - M. M. Ebulue (Universitas Pendidikan Indonesia (UPI), 2023)
This study evaluated the bioactive compounds present in the ethanol leaf extract of Eucalyptus tereticornis as well as its antioxidant potential using standard biochemical methods. The leaf extract contains rich number of bioactive compounds (Phenol 109.41± 0.10GAE/g, Flavonoids 33.10± 0.01mgCE/g, Beta-carotene 3.16± 0.00mg/g and Lycopene 0.32± 0.00mg/g). The antioxidant potentials were evaluated using 2, 2-diphenyl-1-picrylhydrazyl (DPPH) radical, iron-reducing power, inhibition of lipid peroxidation, and nitric oxide scavenging antioxidant systems. The antioxidant activities of the plant extract increased with an increase in concentration. The extract showed high potency in DPPH and nitric oxide free radical scavenging activity compared with the known vitamin C antioxidant potentials. A high reducing power indicative of a high proton (H+) donating potential with a high inhibition of lipid peroxidation portrays a high potent antioxidant activity that protects cells from deleterious effects of free radicals which accounts for its medicinal use. The general results indicated that the plant is rich in bioactive compounds which are believed to have contributed to the high antioxidant activities observed and its medicinal value.